Effectiveness of early hematopoietic stem cell transplantation in preventing neurocognitive decline in aspartylglucosaminuria: A case series. Issue 1 (5th May 2021) - Selvanathan, Arthavan; Kinsella, Jane; Moore, Francesca; Wynn, Robert; Jones, Simon; Shaw, Peter J.; Wilcken, Bridget; Bhattacharya, Kaustuv
Abstract: Aspartylglucosaminuria (AGU) (OMIM #208400) is a recessively inherited disorder of glycoprotein catabolism, a subset of the lysosomal storage disorders (LSDs). Deficiency of the enzyme glycosylasparaginase (E.C. 3.5.1.26) leads to accumulation of aspartylglucosamine in various organs and its excretion in the urine. The disease is characterized by an initial period of normal development in infancy, a plateau in childhood, and subsequent regression in adolescence and adulthood. No curative treatments are currently available, leading to a protracted period of significant disability prior to early death. Hematopoietic stem cell transplantation (HSCT) has demonstrated efficacy in other LSDs, by providing enzyme replacement therapy in somatic viscera and decreasing substrate accumulation. Moreover, donor‐derived monocytes cross the blood‐brain barrier, differentiate into microglia, and secrete enzyme in the central nervous system (CNS). This has been shown to improve neurocognitive outcomes in other LSDs. The evidence to date for HSCT in AGU is varied, with marked improvement in glycosylasparaginase enzyme activity in the CNS in mice models, but varying neurocognitive outcomes in humans. We present a case series of four children with AGU who underwent HSCT at different ages (9 years, 5 years, 5 months, and 7 months of age), with long‐term follow‐up post‐transplant (over 10 years). These cases demonstrate similar neurodevelopmental heterogeneity based on formal developmental assessments. The third case, transplanted prior to the onset of neurocognitive involvement, is developing normally despite a severe phenotype in other family members. This suggests that further research should examine the role of early HSCT in management of AGU.